Numerical modelling approach for considering effects of surface integrity on micro-crack formation. (December 2020) - Nafar Dastgerdi, J.; Sheibanian, F.; Remes, H.; Lehto, P.; Hosseini Toudeshky, H.
Abstract: This work studies the simultaneous effects of surface roughness and residual stress on the micro-crack formation under peak load conditions. The manufacturing process of e.g. steel components influences the surface topography and the material microstructure. These changes affect the surface integrity, which in turn define the component's mechanical properties such as fatigue strength. This paper introduces an efficient finite-element based approach to analyze the influence of surface roughness, residual stress, and microstructural composition on micro-crack formation mechanism during monotonic peak load. The proposed approach combines surface roughness profiles, a ductile fracture criterion and a layer-wise residual stress definition for an approach that is suitable for surface integrity analysis. An inverse numerical-experimental approach is presented for the calibration of the ductile fracture criterion under different stress states. The developed approach is applied to a sandblasted S690 high strength steel, in which the surface integrity has been altered by the manufacturing process. The possibility of crack initiation in the vicinity of critical micro notches is investigated, and the influence of surface roughness and residual stresses is studied. The proposed modelling principles and calibration approach can be employed for other materials and surface profiles. Graphical abstract: Unlabelled Image Highlights: A new finite element modelling approach has been developed to account for the influences of surface roughness, residual stress, and material effect simultaneously on the formation of micro-cracks. A layer-wise residual stress modelling and a ductile fracture criterion with a new special calibration approach are introduced. Holistic understating about the role of surface roughness on the crack formation is provided. The proposed modelling principles and calibration approach can be employed for other materials and surface profiles.